2020
DOI: 10.1142/s0129055x20500336
|View full text |Cite
|
Sign up to set email alerts
|

On the regularity of Cauchy hypersurfaces and temporal functions in closed cone structures

Abstract: We complement our work on the causality of upper semi-continuous distributions of cones with some results on Cauchy hypersurfaces. We prove that every locally stably acausal Cauchy hypersurface is stable. Then we prove that the signed distance dS from a spacelike hypersurface S is, in a neighborhood of it, as regular as the hypersurface, and by using this fact we give a proof that every Cauchy hypersurface is the level set of a Cauchy temporal (and steep) function of the same regularity of the hypersurface. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The interior IntX of a set X ⊂ M might be denoted X for shortness. The reader is referred to [22,24] for the C 0 causality theory and to [23] for all the other conventions adopted without mention in this work.…”
Section: Preliminaries and Proofmentioning
confidence: 99%
See 1 more Smart Citation
“…The interior IntX of a set X ⊂ M might be denoted X for shortness. The reader is referred to [22,24] for the C 0 causality theory and to [23] for all the other conventions adopted without mention in this work.…”
Section: Preliminaries and Proofmentioning
confidence: 99%
“…Galloway, Ling and Sbierski [11] proved that in globally hyperbolic spacetimes timelike completeness guarantees C 0 inextendibility, a result improved by Minguzzi and Suhr [25] who showed that global hyperbolicity could in fact be dropped. Bernard and Suhr [2,3] and Minguzzi [22,24] obtained several results on regularity of time functions and Cauchy hypersurfaces under even weaker conditions. Grant, Kunzinger, Sämann and Steinbauer clarified properties and pathologies of the chronological future under low regularity [13].…”
Section: Introductionmentioning
confidence: 99%
“…These are Cauchy hypersurfaces which are also Cauchy hypersurfaces for some metric g g with strictly wider lightcones than g. Bernard and Suhr [7,Corollary 2.4] show that a smooth spacelike Cauchy hypersurface is a stable Cauchy hypersurface and that furthermore one can construct a smooth temporal function such that Σ = t −1 (0) [7, Theorem 1]. A full discussion of this issue is given in the paper by Minguzzi [40]. The approach in [40] is complementary to that in [7] and consists of using topological arguments to show that the causal cones can be widened while preserving the Cauchy property of the hypersurface.…”
Section: The Smooth Settingmentioning
confidence: 99%
“…A full discussion of this issue is given in the paper by Minguzzi [40]. The approach in [40] is complementary to that in [7] and consists of using topological arguments to show that the causal cones can be widened while preserving the Cauchy property of the hypersurface. One may then use the methods of Bernal Sanchez [5] to construct a smooth time function with Σ = t −1 (0) which as shown in [43] is a smooth temporal function for the original spacetime (M, g).…”
Section: The Smooth Settingmentioning
confidence: 99%